Is the weather-induced COVID-19 spread hypothesis a myth or reality? Evidence from the Russian Federation - Lasisi, Taiwo Temitope (Environ Sci Pollut Res Int, 2020)
Several conspiracy theories and hypotheses have been postulated by some individuals from various strata of governance globally concerning the outbreak and spread of the novel coronavirus in the last quarter of 2019. A pertinent hypothesis is the correlation of meteorological elements to the spread of the pandemic. To verify this claim and also confirm the initial findings of Tosepu et al.’s (2020), this study investigated the Spearman rank-order correlation of the number of confirmed COVID-19 cases in the Russian Federation with temperature—maximum, minimum, and average as well as precipitation. Our findings indicated a stronger correlation between average temperature (r(s) = 0.75(***)) and also recorded significant correlations for the other variants of temperature. Hence, the hypothesis of weather-induced COVID-19 spread is substantiated.